The hydrogen sulfide donor, Lawesson's reagent, prevents alendronate-induced gastric damage in rats - Nicolau,L.A.D. (2013)
Our objective was to investigate the protective effect of Lawesson's reagent, an H2S donor, against alendronate (ALD)-induced gastric damage in rats. Rats were pretreated with saline or Lawesson's reagent (3, 9, or 27 µmol/kg, po) once daily for 4 days. After 30 min, gastric damage was induced by ALD (30 mg/kg) administration by gavage. On the last day of treatment, the animals were killed 4 h after ALD administration. Gastric lesions were measured using a computer planimetry program, and gastric corpus pieces were assayed for malondialdehyde (MDA), glutathione (GSH), proinflammatory cytokines [tumor necrosis factor (TNF)-α and interleukin (IL)-1β], and myeloperoxidase (MPO). Other groups were pretreated with glibenclamide (5 mg/kg, ip) or with glibenclamide (5 mg/kg, ip)+diazoxide (3 mg/kg,ip). After 1 h, 27 µmol/kg Lawesson's reagent was administered. After 30 min, 30 mg/kg ALD was administered. ALD caused gastric damage (63.35±9.8 mm2); increased levels of TNF-α, IL-1β, and MDA (2311±302.3 pg/mL, 901.9±106.2 pg/mL, 121.1±4.3 nmol/g, respectively); increased MPO activity (26.1±3.8 U/mg); and reduced GSH levels (180.3±21.9 µg/g). ALD also increased cystathionine-γ-lyase immunoreactivity in the gastric mucosa. Pretreatment with Lawesson's reagent (27 µmol/kg) attenuated ALD-mediated gastric damage (15.77±5.3 mm2); reduced TNF-α, IL-1β, and MDA formation (1502±150.2 pg/mL, 632.3±43.4 pg/mL, 78.4±7.6 nmol/g, respectively); lowered MPO activity (11.7±2.8 U/mg); and increased the level of GSH in the gastric tissue (397.9±40.2 µg/g). Glibenclamide alone reversed the gastric protective effect of Lawesson's reagent. However, glibenclamide plus diazoxide did not alter the effects of Lawesson's reagent. Our results suggest that Lawesson's reagent plays a protective role against ALD-induced gastric damage through mechanisms that depend at least in part on activation of ATP-sensitive potassium (KATP) channels.